Long noncoding RNA ENST00000413528 sponges microRNA‐593‐5p to modulate human glioma growth via polo‐like kinase 1. (28th March 2019) - Zhang, Ren; Wei, Ruo‐Lun; Du, Wei; Zhang, Li‐Wei; Du, Tao; Geng, Ya‐Dong; Wei, Xin‐ting
Summary: Aims: In this study, we examined the expression of lncRNA ENST00000413528 in glioma and determined its role in glioma development. Methods: LncRNA ENST00000413528 was detected in glioma tissues by lncRNA microarray. Then, we performed real‐time PCR, CCK‐8, colony formation assay, flow cytometry, caspase‐3/7 assay and animal experiment to detect the function of ENST00000413528 in glioma after ENST00000413528 knockdown. Subsequent bioinformatics analysis, luciferase reporter assays and RNA immunoprecipitation (RIP) assay western blotting indicated possible downstream regulatory molecules. The expression of PLK1 in glioma tissues was also examined by immunohistochemistry staining. Results: Expression of ENST00000413528 was significantly increased in glioma tissues and LN229 and U251 cells. PLK1 protein could not be detected in peritumoral brain edema (PTBE) tissues; however, it showed an increasing number of positively cytoplasmic stained from WHO‐Grade II to Grade III gliomas. Knockdown of ENST00000413528 in glioma cells inhibited cell proliferation and colony formation abilities, induced the G0/G1 arrest of the cell cycle, and promoted apoptosis. The dual reporter assay and RNA immunoprecipitation assay verified the interaction between ENST00000413528 and miR‐593. We also demonstrated that polo‐like kinase 1 (PLK1) was regulated by miR‐593; PLK1 messenger RNA lacking 3'UTR partially reversed the effects caused by ENST00000413528 knockdown or miR‐593 upregulation. Conclusion: lncRNA ENST00000413528 is closely related to the development of glioma via the miR‐593‐5p/PLK1 pathway.